Analisis Kinerja Turbin Hidrokinetik Dengan Selubung Diffuser Pada Kondisi Yaw Misalignment Berdasarkan Variasi Kecepatan Aliran Air - ., Nasrullah; ., Nofriadi; ., Nasirwan; Leni, Desmarita; Kesuma, Dytchia Septi (Rekayasa Material, Manufaktur dan Energi, 2023)
Yaw Misalignment condition has detrimental effects on the performance and efficiency of hydrokinetic turbines. This phenomenon occurs when the direction of water flow hitting the turbine blades is not aligned with the turbine's movement direction. In this research, an analysis is conducted on the performance of a hydrokinetic turbine equipped with a diffuser shroud under Yaw Misalignment conditions, considering variations in water flow velocity. The dataset used in this study consists of water flow velocity data, yaw angles, tip speed ratio (TSR), and power coefficient (Cp) of a 19.8 cm diameter horizontal-axis hydrokinetic turbine operating under Yaw Misalignment conditions. Experiments were conducted at three water flow velocity levels: 0.7 m/s, 0.9 m/s, and 1.1 m/s. Additionally, yaw angle variations were applied ranging from 0° to 25° at 5° intervals. Data analysis involved the application of Pearson correlation analysis and descriptive statistical analysis to identify the maximum Cp values. The analysis results indicate that the highest maximum Cp value is 0.711, with a tip speed ratio (TSR) of 4.33, achieved at a yaw angle of 0° and a water flow velocity of 0.9 m/s. This indicates that under these conditions, the turbine reaches its peak performance in converting water flow energy into mechanical power.